TINJAUAN MAQASID HUKUM PERKAWINAN ISLAM TERHADAP SYARAT POLIGAMI DALAM KOMPILASI HUKUM ISLAM DI INDONESIA - Anugerah, Ghifari Fajar; Izzuddin, Ahmad; Saiban, Kasuwi (Fakultas Syariah (Syari'ah Faculty ), 2024)
Polygamy in the history of Islamic civilization represents one of the most crucial issues in sexual relations and continues to attract attention among Islamic scholars, particularly feminist thinkers. The debate surrounding polygamy is not only related to textual interpretation but also to its social implications and questions of gender justice, which have prompted Muslim-majority countries, including Indonesia, to establish specific regulations. In Indonesia, polygamy is regulated under Law Number 1 of 1974 on Marriage, Government Regulation Number 9 of 1975, and more comprehensively within the Compilation of Islamic Law (KHI). The KHI outlines several conditions that must be fulfilled, including court authorization, the consent of the existing wife, and the husband’s ability to ensure financial support and justice. This study aims to examine the conformity of these requirements with the maqāṣid al-sharī‘ah in the domain of family law, namely the objectives of Islamic law oriented toward justice and public welfare (maṣlaḥah). The research employs a library-based method by analyzing the regulation of polygamy in Indonesian marriage law and comparing it with the principles of the maqāṣid of Islamic marriage law. The findings indicate that the regulation of polygamy in the KHI encompasses the overall objectives of Islamic marriage law as articulated by Jamaluddin Athiyah. These objectives include maintaining harmonious relations between men and women, safeguarding and preserving lineage, fostering families built on sakīnah (tranquility), mawaddah (affection), and raḥmah (compassion), ensuring the clarity of descent, strengthening religiosity within the family, regulating harmonious familial relations, and guaranteeing financial stability. Thus, the stipulations regarding polygamy in the KHI are not designed to promote the practice widely, but rather serve as a restrictive mechanism intended to protect welfare and prevent harm within the institution of marriage.